Incoming pathogens team up with harmless ‘resident’ bacteria - Venturi, Vittorio (My University, 2014)
The seminar will focus on "Interspecies and interkingdom signaling in plant-associated bacteria". Studies of chemical signaling between plants and bacteria in the past have been largely confined to two models: the rhizobial-legume symbiotic association and pathogenesis between agrobacteria and their host plants. Recent studies are beginning to provide evidence that many plant-associated bacteria undergo chemical signaling with the plant host via low-molecular-weight compounds. Plant-produced compounds interact with bacterial regulatory proteins that then affect gene expression. Similarly, bacterial quorum-sensing signals result in a range of functional responses in plants. This review attempts to highlight current knowledge in chemical signaling that takes place between pathogenic bacteria and plants. This chemical communication between plant and bacteria, also referred to as interkingdom signaling, will likely become a major research field in the future, as it allows the design of specific strategies to create plants that are resistant to plant pathogens.
Interspecies and interkingdom signaling in plant-associated bacteria
Keywords: Microbiología; Biotecnología; Biotechnology; Microbiology; Plant-Bacteria interaction